Changes in carbon pools and biological activities of a sandy loam soil under medium‐term conservation agriculture and diversified cropping systems - Parihar, Chiter Mal; Jat, Shankar Lal; Singh, A.K.; Datta, A.; Parihar, Muli D.; Varghese, E.; Bandyopadhyay, K.K.; Nayak, HS; Kuri, B.R.; Jat, Mangi Lal (Wiley, 2018)
Conservation agriculture (CA) practices such as zero tillage (ZT) and permanent raised beds (PB) accelerate deposition of soil organic matter and augment associated biological properties of soil through enhanced inputs of organic carbon. However, the potential benefit of CA under intensive cereal‐based systems for key soil health indicators (such as carbon pools and biological activities) is only partially known. Therefore, we analysed the effect of three medium‐term tillage practices and four intensive crop rotations on selected soil organic carbon pools and microbial properties. The tillage practices consist of ZT, PB and conventional tillage (CT) in main plots and four crop rotations (MWMb, maize–wheat–mungbean; MCS, maize–chickpea–Sesbania; MMuMb, maize–mustard–mungbean; MMS, maize–maize–Sesbania) in subplots. The experimental design was split‐plot with three replications. After 6 years, we observed a significant positive effect of CA practices on soil organic carbon (SOC) content, labile SOC fractions, soil microbial biomass carbon (MBC) and dehydrogenase activity (DHA). The total organic carbon (TOC) was greatly affected by medium‐term tillage and diversified cropping systems; it was larger for CA and MCS and MWMb systems. The interaction effect between tillage and cropping systems for SOC content was not significant at all soil depths. Significantly larger contributions (8.5–25.5%) of labile SOC pools to TOC at various soil depths were recorded in PB and ZT. There was a significant positive effect of CA practices and diversified crop rotations on MBC and DHA at all the soil depths and sampling times, but the interaction effect between tillage and cropping systems was not significant. Thus, our medium‐term (≥ 5‐years) study showed that the combination of CA (PB and ZT) practices and appropriate choice of rotations (MCS and MWMb) appears to be the most appropriate option for restoration and improvement of the soil health of light‐textured Inceptisols through the accumulation of soil organic matter (SOM) and improvement in soil biological properties.